PEMANFAATAN LIMBAH KELAPA SAWIT DI KABUPATEN LANGKAT - Abdurrozzaq Hasibuan; Cindy Chairunnisa; Ayu Amanda Siregar; Ainun Zariah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The oil palm plantation sector is one of the important sectors in the country's economy, making a significant contribution to national income and employment absorption. In recent years, the increase in palm oil production has led to an increase in the volume of palm oil waste produced in Indonesia. This large amount of waste creates a serious challenge in its management, because it can contaminate the environment, including groundwater and rivers, as well as threaten biodiversity. This research aims to analyze and identify how to use palm oil waste in Indonesia. This research was carried out using literature study techniques where data was taken from journals and articles that had gone through various screenings, one of which was screening by ensuring the linkage between the title and the reference of the article used as well as using the references from the appropriate journals. Results Palm oil waste has quite promising potential for utilization in various selectors such as developmental alternative energy sources and agricultural selectors. In alternative energy source selectors, namely one of them is biomass fuel which functions as an alternative for fuel for power generation and in agriculture selectors are commonly used as organic fertilizer ingredients. In the breeding selector it can be used as additional feed and additional nutrition for livestock. Conclusion: Based on the journals that have been studied, it is concluded that the utilization of palm oil waste in Langkat Regency is partly by turning the waste into compost for plants/plantation as well as turning palm oil waste into a product that has market value to increase the economic level of local people.